Informal Payments in Healthcare Services: A Literature Review - Doğancan Çavmak; Sait Söyler; Cenk Teker (Association of Nurse Managers, 2019)
INTRODUCTION: Introduction: Health systems are a sub-system directly affected by economic systems. Therefore, health systems may change as the economic systems of countries change. Regardless of which economic system is adopted and how this system is circulating to the health system, problems such as access to health, justice, equity and quality are the main problems that should be solved in health systems. As systems fail to solve such problems, individuals within the system begin to implement their own methods with the aim of eliminating/abusing deficits in the system. In this sense, informal payments can be seen as a tool for the use of such weaknesses for both health workers and healthcare consumers. Aim: The aim of this study is to draw a frame of the world wide on informal payments which may cause various injustices and degeneration of system in terms of access to health systems and quality of health services. METHODS: Methods: Systematic literature review was preferred as a method in the study and 20 studies which met inclusion criterias were included in the study. RESULTS: Results: Informal payments have a high prevalence especially in post-communist and under developed countries and the reasons of these results were examined. DISCUSSION AND CONCLUSION: Conclusion: it is recommended that a number of studies should be carried out to legitimize these kind of payments, and to monitor the results of the precautions taken into consideration in Turkey.